Pendugaan umur simpan kerupuk amplang ikan nila dengan berbagai jenis kemasan menggunakan metode pendekatan kadar air kritis - Nur Wijayanti; Ienas Nadiya; Dian Novitasari; Laksmi Putri Ayuningtyas; Rumpoko Wicaksono (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Shelf life is an important thing to know and an indication of product safety. The shelf life of Poklahsar Bunda Madani’s tilapia fish amplang crackers is unknown. Determining the shelf life of tilapia fish amplang crakers using Accelerated Shelf Life Testing (ASLT) method with critical water content and several packages to determine the appropiate type of packaging. This study aims to 1) determine the shelf life of tilapia fish amplang crackers, 2) determine the effect of various types of packaging on the shelf life of tilapia fish amplang crackers using the estimation of critical moisture content, and 3) determine the best type of packaging that can maintain the shelf life of tilapia fish amplang crackers. The results of reseach estimated the shelf life of tilapia fish amplang crackers in polypropylene plastic packaging was 179 days (5 months), with metal plastic packaging it was 266 days (8 months), and with aluminium foil it was 322 days (10 months). Products packaged in packaging with low gas, light, and water vapor permeability make the product long lasting. Based on these results, aluminium foil has the lowest permeability and being the best packaging.